Risk assessment of flash flood potential in the humid tropics Indonesia: a case study in Tamiang River basin. (3rd November 2021) - Azizah, Cut; Pawitan, Hidayat; Dasanto, Bambang Dwi; Ridwansyah, Iwan; Taufik, Muh
Assessment of areas prone to flash flood is a major challenge especially in limited data basin. This study aims to assess the areas vulnerable to flash flood in the Tamiang basin, Indonesia based on the flash flood potential index. The index depends on the physiographic influencing factors. Here, we improved the index by integrating antecedent precipitation index (API) and curve number (CN) as influencing factors and using an analytical hierarchy process (AHP) to determine the weighted factor. Historical flash flood locations were used to verify the index. The results show that the highest flash flood prone occurs in areas with high CN and API. Our findings were consistent with the historical flash flood events in the basin; therefore the use of weighted factor based on AHP is reliable. Moreover, our findings provide policymakers with the information needed to choose an appropriate management strategy to tackle possible future flash flood events.